A Digital Commentary to Karl Kraus’s ’Dritte Walpurgisnacht’ (1933) - Oberreither, Bernhard (Wiener Digitale Revue, 2024)
peer-reviewed Recently, the digital edition of Karl Kraus’s Dritte Walpurgisnacht was extended by an extensive commentary, shedding light on obscure text passages and situating the text against its historical and cultural background. The endeavor to write this commentary was set in a specific context that was shaped by a number of factors. This essay’s goal is twofold: it aims to present the scope and functionality of the commentary; at the same time, it intends to examine the factors that constitute the context of its creation – the discussions on commentary in the field of scholarly edition, the changed circumstances under the digital paradigm, the challenges of (and in some ways objections against) commenting on a work by Karl Kraus –, and how the commentary to Dritte Walpurgisnacht relates to them. Vor kurzem wurde die digitale Ausgabe von Karl Kraus’ Dritter Walpurgisnacht um einen ausführlichen Stellenkommentar erweitert, der schwer verständliche Textpassagen beleuchtet und den Text vor seinem historischen und kulturellen Hintergrund verortet. Die Erstellung dieses Kommentars stand in einem spezifischen Kontext, der durch eine Reihe von Faktoren geprägt war. Der vorliegende Aufsatz verfolgt ein doppeltes Ziel: Er will den Umfang und die Funktionalität des Kommentars darstellen und zugleich die Faktoren beleuchten, die den Entstehungskontext ausmachen – die Diskussionen um den Kommentar innerhalb der Editionswissenschaft, die durch die digitale Wende veränderten Umstände, die Herausforderungen der Kommentierung eines Werkes von Karl Kraus sowie die möglichen Einwände dagegen –, und skizzieren, wie sich der Kommentar zur Dritten Walpurgisnacht zu ihnen verhält.